2011
DOI: 10.1002/etc.691
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the acute toxicities of novel algicides, thiazolidinedione derivatives TD49 and TD53, to various marine organisms

Abstract: Acute toxicity assessments of new algicides, thiazolidinedione derivatives TD49 and TD53, to the marine ecological system were conducted. The toxicity assessments were performed using two of the new International Organization for Standardization (ISO) standard methods employing Ulva pertusa Kjellman and three species representative of the marine ecological system, with the results compared by calculating the 50% effective concentration (EC50), 50% lethal concentration (LC50), no-observed-effect concentration (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Zhou et al [ 44 ] indicated the 24h LC 50 of garlic solution to M. mongolica and B. plicatilis were 0.33 and 0.17% (v/v), respectively. Kim et al [ 45 ] reported the 72h LC 50 of thiazolidinedione derivatives TD49 to P. olivaceus was 0.58 μmol/L. Therefore, the algicidal substances of bacterium Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al [ 44 ] indicated the 24h LC 50 of garlic solution to M. mongolica and B. plicatilis were 0.33 and 0.17% (v/v), respectively. Kim et al [ 45 ] reported the 72h LC 50 of thiazolidinedione derivatives TD49 to P. olivaceus was 0.58 μmol/L. Therefore, the algicidal substances of bacterium Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, rapid increases in agriculture and industrial processes, as well as population booms, have substantially increased the frequency, extent, and inducing factors of red tide globally. This increase in red tides may pose a threat to ecology, the aquaculture industry, and human health [6]. Many physiological and ecological investigations have been performed to reduce the severity of losses to coastal fisheries caused by red tides [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In the late 1990s, thiazolidinedione (TD) was developed as an adjunctive therapy for diabetes. TD acts by binding to peroxisome proliferator-activated receptors (PPAR) in the nucleus [6]; it has been shown to be highly effective and selective against harmful algae, with a half maximal inhibitory concentration (IC 50 ) in the nanomolar range [7]. The derivative TD 49 (TD 49 ) is a newly synthesized algicide that shows high toxicity at low concentrations of 0.1–2 μM against harmful algal species including Cochlodinium polykrikoides , Chattonella marina , and Heterosigma akashiwo [7], as well as very low toxicity to non-harmful algae, even at concentrations of over 100 μM [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations imply that TD49 is an effective algicidal compound with sufficient environmental safety. Despite the aforementioned advantages, the potential for toxicity to other marine organisms at the currently employed TD49 concentrations still exists (Kim et al, 2011). By encapsidation within VLPs, the specificity and potency of TD49 at safer concentrations of < 1.0 μM might be achieved.…”
Section: Discussionmentioning
confidence: 99%